Brain Endothelial Cells Regulate Glucagon-Like Peptide 1 Entry Into the Brain via a Receptor-Mediated Process - Fu, Zhuo; Gong, Liying; Liu, Jia; Wu, Jing; Barrett, Eugene J.; Aylor, Kevin W.; Liu, Zhenqi (Frontiers in Physiology, 2020)
Glucagon-like peptide 1 (GLP-1) in addition to regulating glucose-dependent insulin and glucagon secretion exerts anorexic and neuroprotective effects. While brain-derived GLP-1 may participate in these central actions, evidence suggests that peripherally derived GLP-1 plays an important role and GLP-1 analogs are known to cross the blood brain barrier. To define the role of brain microvascular endothelial cells in GLP-1 entry into the brain, we infused labelled GLP-1 or exendin-4 into rats intravenously and examined their appearance and protein kinase A activities in various brain regions. We also studied the role of endothelial cell GLP-1 receptor and its signaling in endothelial cell uptake and transport of GLP-1. Systemically infused labelled GLP-1 or exendin-4 appeared rapidly in various brain regions and this was associated with increased protein kinase A activity in these brain regions. Pretreatment with GLP-1 receptor antagonist reduced labelled GLP-1 or exendin-4 enrichment in the brain. Sub-diaphragmatic vagus nerve resection did not alter GLP-1-mediated increases in protein kinase A activity in the brain. Rat brain microvascular endothelial cells rapidly took up labelled GLP-1 and this was blunted by either GLP-1 receptor antagonism or protein kinase A inhibition but enhanced through adenylyl cyclase activation. Using an artificially assembled blood brain barrier consisting of endothelial and astrocyte layers, we found that labelled GLP-1 time-dependently crossed the barrier and the presence of GLP-1 receptor antagonist blunted this transit. We conclude that GLP-1 crosses the blood brain barrier through active trans-endothelial transport which requires GLP-1 receptor binding and activation.